Laura Ingalls Wilder a biography - Anderson, William (New York, NY : HarperCollins, 2007)
A biography of the writer whose pioneer life on the American prairie became the basis for her "Little House" books.
Pioneer family -- Indian territory -- "Give them a covered wagon and they're ready to go!' -- Along plum creek -- Year in Burr oak -- Going West again -- Dakota territory -- Prairie girl -- Teaching, courtship and marriage -- "We want to see the world!' -- To the land of the big red apple -- Rocky ridge farm -- Gem city of the Ozarks -- "As a farm woman thinks" -- "Good times on the farm!" -- "Stories that had to be told" -- "Our quiet home" -- Rich harvest.
Includes index.
1000L
Keywords: Wilder, Laura Ingalls -- 1867-1957 -- Juvenile Literature; Authors, American -- 20th century; Frontier and pioneer life -- United States; Children's stories -- Authorship; Authors, American; Frontier and pioneer life